Cloud internet of things-based cyber-physical system for microalgae integrated-aquaculture recirculating system in Sarawak - Kee, Keh-Kim; Lau, John Sie Yon; Yong, Alan Huong Ting (International Journal of Electrical and Computer Engineering (IJECE), 2026)
The escalating demand for high-quality protein has driven commercial aquaculture's growth, and microalgal biomass shows potential to support this sector and contribute to global food security. Digitalizing integrated microalgal-aquaculture systems can significantly enhance sustainable protein production. Enabling technologies like the internet of things (IoT) and cyber-physical systems (CPS) are crucial for creating resilient aquaculture systems that ensure profitability, ecosystem health, and climate adaptability. However, applying cloud IoT and CPS solutions in the microalgae industry, especially the integrated microalgae and prawn farms remain underexplored. This work aims to develop a smart system for real-time monitoring and analysis of integrated microalgae and prawn farms in Sarawak, supported by an intelligent decision-support system. Utilizing a hybrid cloud-fog architecture, the system ensures efficient data acquisition, storage, and analysis and provides real-time monitoring through various user interfaces. Deployed in the plant site for over three months, the proposed system has proven effective in enhancing process efficiency and functionality, offering valuable reference in sustainable aquaculture for future enhancements such as multi-sensor and multi-site deployment in other farming systems to promote holistic environment sustainability and digital transformation.